About physical parameters of experimental reactor- stellarator in the conditions of ambipolarity of neoclassical transport fluxes - Rudakov, V.A. (Вопросы атомной науки и техники, 2012)
Parameters of an experimental stellarator reactor operating under conditions of ambipolarity of neoclassical transport fluxes are calculated with the use of a space-time numerical code. Dimensions of the system and the confinement magnetic field are taken the same as in the ITER tokamak reactor. The paper shows a possibility of engineering development of an experimental stellarator reactor with parameters comparable to these of an experimental tokamak reactor.